Spectrum of Lesions in the Urinary Bladder: A Histopathological Study in a Tertiary Level Hospital - Poudel, Suman; Ranabhat, Sunita; Shahi, Sharmila; Pun, Gita (Journal of College of Medical Sciences-Nepal, 2023)
Background: Urinary Bladder cancer is the 7th most common cancer worldwide, with an estimated 260,000 new cases occurring each year in men and 76,000 in women. 90% of the bladder tumors are of urothelial origin. Cystoscopic examination has a limited role in staging process for which transurethral resection (TURBT) of visible tumor down to the base is required which can accurately assess depth of tumor invasion. Aim & Objectives: The aim is to study the spectrum of urinary bladder lesions according to World Health Organization / International Society of Urological Pathology consensus classification and to determine age and sex distribution of urothelial tumors. Material & Method: Study included 55 TURBT specimens, conducted over a period 12 months, extending from January 2022 to December 2022. Hematoxylin & Eosin (H&E) stained sections were examined for morphologic diagnosis of urothelial lesions. Results: In our study, there was male preponderance with ratio of 3.2:1. Among 55 cases studied, 34.55% cases were diagnosed as invasive urothelial carcinoma, 27.27% cases were of non-invasive urothelial carcinoma, 16.36% cases were of benign urothelial neoplasm and 16.36% cases were of non-neoplastic lesions in urinary bladder. There were also 1.82% cases of adenocarcinoma, metastasis and non-diagnostic each in our study. Amongst invasive carcinoma high grade were encountered most (30.91%) cases. Maximum numbers of urothelial neoplasms (25.45%) were seen in 71-80 years of age group. Conclusion: This study revealed that neoplastic lesions are more common than non-neoplastic lesions. Urothelial tumors are seen commonly in seventh decade with overall male predominance. Also this study, documents a high frequency of invasive than non-invasive type of urothelial neoplasm.